My favourite birds picture book (Heaven publishers Lahore, 1990)
"My Favourite Birds" is a charming picture book that introduces young readers to a variety of fascinating bird species. Through vibrant illustrations and engaging text, it highlights unique characteristics and behaviors, fostering a love for nature and encouraging curiosity about wildlife. Perfect for early learners, this book invites exploration and appreciation of the avian world.